A Methods engineering study on Yoshita Corporation - Adrias, Maria Karla (College of Engineering, 2003)
This Methods Engineering study on Yoshita Corporation aims to improve the production system of the current transformer section. More specifically, improvements in productivity through changes in the methods, layout, wage payment, and general environment are sought. Through observations and analysis, eleven root problems were identified and are addressed in this study namely : insufficient lighting, poor ventilation, distracting noise, delay due to filling up forms, delay due to excessive transportation and storage, significant amount of wasted material, high daily quotas, rework operations performed in between regular work pattern, low machine capacity, long and continuous working hours, and ineffective compensation plans. For each of these problems, alternatives were generated and chosen. Among them are : enclosing the odor source, line balancing with accompanying change in layout, hiring of a rework employee, purchase of a third coil winding machine and adoption of an incentive wage payment scheme. Implementation of these alternatives can lead to increased profits due to the rise in daily production capacity from 16,000 units to 24,000 units, key improvements in productivity manifested by the 30.5 percent reduction in cycle time and the elimination of unnecessary storage, transportation, and filling out forms, and finally, improved worker satisfaction brought about by a better work environment, incentive plan, and new work schedule.